2000
DOI: 10.1096/fj.00-0031com
|View full text |Cite
|
Sign up to set email alerts
|

The P2 purinergic receptors of human dendritic cells: identification and coupling to cytokine release

Abstract: We investigated the expression of purinoceptors in human dendritic cells, providing functional, pharmacological, and biochemical evidence that immature and mature cells express P2Y and P2X subtypes, coupled to increase in the intracellular Ca(2+), membrane depolarization, and secretion of inflammatory cytokines. The ATP-activated Ca(2+) change was biphasic, with a fast release from intracellular stores and a delayed influx across the plasma membrane. A prolonged exposure to ATP was toxic to dendritic cells tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
140
2
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(157 citation statements)
references
References 54 publications
10
140
2
5
Order By: Relevance
“…Human dendritic cells were found to express mRNA for P2X1, P2X4, P2X5, and P2X7 as well as for P2Y 1 , P2Y 2 , P2Y 4 , P2Y 6 , P2Y 11 , and P2Y 14 receptors [123][124][125][126]. The expression of P2X7 on protein level in DCs during immune responses was suggested by Buell et al who observed immunopositive staining within human tonsils [127].…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Human dendritic cells were found to express mRNA for P2X1, P2X4, P2X5, and P2X7 as well as for P2Y 1 , P2Y 2 , P2Y 4 , P2Y 6 , P2Y 11 , and P2Y 14 receptors [123][124][125][126]. The expression of P2X7 on protein level in DCs during immune responses was suggested by Buell et al who observed immunopositive staining within human tonsils [127].…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…It is known that ATP activates P2X 7 receptors in microglial cells in which it mediates cytotoxic responses and cytokine release. This suggests that it may have an important role in immunomodulation Di Virgilio et al, 1998;Ferrari et al, 2000;Inoue, 2002). There is increasing evidence that microglial cells are related to a number of physio-pathological events in the retina when massive cell death occurs (Schnitzer and Scherer, 1990;Milligan et al, 1991;Thanos, 1991;Frade and Barde, 1998).…”
Section: Identification Of Retinal Cell Types Expressing Permeabilizimentioning
confidence: 99%
“…There are several precedents for this possibility. Monocyte-derived dendritic cells have been shown to express a number of P2Rs of both the P2X and the P2Y series (11,12). Exposure of monocyte-derived dendritic cells to ATP results in up-regulation of CD54 and MHC class II molecules, induces secretion of IL-12, and augments stimulatory capacity for allogeneic T cells (11,13).…”
mentioning
confidence: 99%
“…Exposure of monocyte-derived dendritic cells to ATP results in up-regulation of CD54 and MHC class II molecules, induces secretion of IL-12, and augments stimulatory capacity for allogeneic T cells (11,13). Exposure of LPS-matured dendritic cells to ATP induces the release of IL-1␤ and TNF-␣ (12). In combination with TNF-␣, ATP has been shown to increase the expression of CD80, CD83, and CD86 in monocyte-derived dendritic cells (11).…”
mentioning
confidence: 99%